Modelling atmospheric and hydrologic processes for assessment of meadow restoration impact on flow and sediment in a sparsely gauged California watershed. Issue 7 (20th May 2013) - Ohara, N.; Kavvas, M. L.; Chen, Z. Q.; Liang, L.; Anderson, M.; Wilcox, J.; Mink, L.
Abstract The restoration of meadowland using the pond and plug technique of gully elimination was performed in a 9‐mile segment along Last Chance Creek, Feather River Basin, California, in order to rehabilitate floodplain functions such as mitigating floods, retaining groundwater, and reducing sediment yield associated with bank erosion and to significantly alter the hydrologic regime. However, because the atmospheric and hydrological conditions have evolved over the restoration period, it was difficult to obtain a comprehensible evaluation of the impact of restoration activities by means of field measurements. In this paper, a new use of physically based models for environmental assessment is described. The atmospheric conditions over the sparsely gauged Last Chance Creek watershed (which does not have any precipitation or weather stations) during the combined historical critical dry and wet period (1982–1993) were reconstructed over the whole watershed using the atmospheric fifth‐generation mesoscale model driven with the US National Center for Atmospheric Research and US National Center for Environmental Prediction reanalysis data. Using the downscaled atmospheric data as its input, the watershed environmental hydrology (WEHY) model was applied to this watershed. All physical parameters of the WEHY model were derived from the existing geographic information system and satellite‐driven data sets. By comparing the prerestoration and postrestoration simulation results under the identical atmospheric conditions, a more complete environmental assessment of the restoration project was made. Model results indicate that the flood peak may be reduced by 10–20% during the wet year and the baseflow may be enhanced by 10–20% during the following dry seasons (summer to fall) in the postrestoration condition. The model results also showed that the hydrologic impact of the land management associated with the restoration mitigates bank erosion and sediment discharge during winter storm events. Copyright © 2013 John Wiley & Sons, Ltd.